Compression Buckling Response of Tow-placed, Variable Stiffness Composite Panels with Sine Curved and Tangent Curved Fibers. Issue 9 (November 2013) - Yongli, Qin; Yingdan, Zhu; Yueping, Yu; Chun, Yan; Xiaoqing, Zhang; Xinyu, Fan
Tailoring of composite laminated panels by Variable Angle Tow (VAT) steering fibers in their optimal spatial orientations provides a unique opportunity to maximize performance. Increased buckling response of the laminates by VAT steering technique may directly provide significant weight savings by redistributing loads in a benign manner. The aim of this work is to design tow-placed, variable stiffness composite panels with resistance to buckling by steering sine curved and tangent curved fibers. Buckling behaviors of two types of VAT panels and three typical types of straight fiber panels ([45/-45/0/90]s, [±45]2s, [0/90]2s) are investigated by finite element numerical simulations. It is found that the VAT panels with sine curved and tangent curved fibers show much better buckling performance to traditional straight fiber panels, with 9.25%-30.75% and 8.18%-29.47% improvement in buckling load respectively and a more uniform stress distribution. These results demonstrate that the design of composite laminated panels with sine curved and tangent curved fiber formats has the potential for buckling performance improvements in structural efficiency, and sine curved fibers may enhance buckling property of composite laminates better than tangent curved fibers do.